PENGARUH STRATEGI PLANTET QUESTIONS TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN 1 PERESAK KECAMATAN NARMADA - Naili Irmayanti; Khairun Nisa; Husniati Husniati (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
This study aims to determine whether there is influence of active learning strategy type plantet questions on the results of IPS students learning grade IV SDN 1 Peresak Lesson Year 2017/2018. The method of research, is a quasi-type experimental experimental design nonequivalent control group design. The population in this study, is all students of grade IV SDN 1 Peresak. The researcher used saturated sampling technique which means, the whole population was used as the research sample which amounted to 49 students, where the class IV A as the experimental class and class IV B as the control class. Data collection using IPS learning result test. The data obtained is processed by one way analysis technique of anava. Before the first anova test done the prerequisite test that is normality and homogeneity. The results showed the mean values of pretest and posttest of the experimental class and control classes respectively, were 49.61 and 44.34 and 77.87 and 57.82 respectively. The data of this research are normal and homogeneous distribution with 5% significance level, where the result of hypothesis test with one path analysis technique shows that Fcount> Ftable is 37,83> 4,04. In accordance with the criteria of hypothesis testing, that is if Fcount> Ftable then, Ho is rejected Ha accepted so, there is Influence of active learning strategy type plantet questions on the results of learning IPS fourth grade students SDN 1 Peresak Lesson 2017/2018.